Lightning generated electric field over land and sea at Northern Region of Peninsular Malaysia: Measuring Setup - Ahmad Muhyiddin Yusof; Zulkurnain Abdul-Malek; Chin-Leong Wooi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Lightning is the transfer of significant charge between two charged object, it can appear between cloud-to-cloud, cloud-to-air and cloud-to-ground. All lightning activities are correlated with charge movement and therefore, it can be studied using measurement of electrostatic field (slow field changes), radiation field (fast field changes) and magnetic field affiliated with charge movement. The measuring equipment was a parallel flat plate and vertical whip antenna with an analog filter buffer circuit, connected to a digital high speed oscilloscope. In principle, both antenna have a similar measuring operation, with the exclusion of the antennas dimension, mode of transient recoder and the association of circuitry characteristic (decay time constant). This measurement setup are commonly used to perform electric field characterization related to various lightning events such as as preliminary breakdown, stepped leader, return stroke, subsequent return stroke, dart leader, dart-stepped leader, narrow bipolar pulses and cloud activity between strokes, such as regular pulse trains, K and M changes and chaotic pulse trains. The measurement systems are located very close to the sea, with respect in obtaining a perspicuous explaination of lightning propagation effects on sea instead on land. Noise-distorted effects in data captured usually introduce in a noisy environment or when the lightning strike far from the measurement station, thus the data gathered from the measurement need to be filter using MATLAB computer simulation before conducting further analysis. A promising wavelet 1-D technique, then, were used in signal denoising process rather using conventional filtration. In this works, the state of art in measuring vertical component of electric field focalized sea area during the thunderstorm days been demonstrate and explained.